Solvothermal fabrication of thin Ag nanowires assisted with AAO. Issue 85 (30th August 2016) - Song, Mingxia; He, Xin; Zhang, Chaozhi; Chen, Mindong; Huang, Caijin; Chen, Fenghua; Qiu, Hui
Abstract : Silver nanowires were synthesized using solvothermal method assisted with AAO. AAO here is playing a role as a heterogeneous medium that can promote PVP molecules to form into one dimensional template and thus guiding the growth of Ag nanowires. Abstract : Single crystalline thin silver nanowires with a diameter of ∼45 nm were synthesized using a solvothermal method assisted with an anodic aluminum oxide (AAO) template. AAO here is not playing a role as a hard template but as a heterogeneous medium whose porous structure can promote PVP molecules to form into a one dimensional template. This soft template can effectively guide the growth of Ag nanowires and thus reduce the reaction time considerably. We further investigated the influences of reaction time, temperature and ratio of PVP to AgNO3 on the formation of Ag nanowires by SEM and UV-Vis absorption spectra characterization. The reaction mechanism was also demonstrated by TEM analysis. Our work may provide a better way to control the synthesis of metallic nanostructures in chemical solution.